Edaravone ameliorates valproate-ınduced gingival toxicity by reducing oxidative-stress, ınflammation and tissue damage - Oktay, Şehkar; Alev, Burcin; Koc Ozturk, Leyla; Tunali, Sevim; Demirel, Sezin; Emekli Alturfan, Ebru; Tunali-Akbay, Tugba; Akyuz, Serap; Yanardag, Refiye; Yarat, Aysen (My University, 2016)
Valproic acid (2-n-propylpentanoic acid, VPA), the most widely used antiepileptic drug, has potential adverse effects and it can disrupt the oxidant and antioxidant balance. Edaravone (3-methyl-1-phenyl-2-pyrazoline-5-one, EDA) is a potent free radical scavenger. In this study, the effect of EDA on gingiva in VPA induced toxicity was investigated. Female Sprague Dawley rats were randomly divided into four groups: control group, EDA (30 mg/kg/day) given group, VPA (0.5 g/kg/day) given group, and VPA+EDA (in same dose and time) given group. EDA and VPA were given intraperitoneally for seven days. Total protein, lipid peroxidation (LPO), sialic acid (SA) and reduced glutathione (GSH) levels and catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidase (GPx), superoxide dismutase (SOD), myeloperoxidase (MPO), alkaline phosphatase (ALP), acid phosphatase (ACP), sodium potassium ATPase (Na+/K+-ATPase) and tissue factor (TF) activities were determined in gingiva homogenates. The VPA-induced increases were statistically significant for MPO (p<0.01), ACP (p<0.01), Na+/K+-ATPase (p<0.05) and TF (p<0.01) activities, but not for LPO level and ALP activities. EDA treatment markedly blunted all such elevated anomalies. Conclusively, VPA induced oxidative and inflammatory gingival tissue damage, reactions that were appreciably reversed by concurrent administration of EDA.
Keywords: Gingiva, valproic acid, edaravone, oxidative stress, inflammation